ENT300 Fundamental of Entrepreneurship. Business Plan : Healthy LifeStyle Center Company / Cynthia Pia Ak Latit... [et al.] - Latit, Cynthia Pia; James Mandau, Spheniah; Giri, Sindra; Nanang, Rosie; Ramlee, Afirah Shafiqnas; Arun, Benya (2014)
The name of our company is Healthy LifeStyle Centre (H.L.C). The business is in form of partnership which consists of six members. Each partner contributes certain amount of capital as agreed in agreement for this business. All partners give their attention for this business and are entitled to participate in the business management. We agreed that Cynthia Pia ak Latit as the General Manager, Sindra ak Giri as the Administrative Manager, Spheniah ak James Mandau as the Marketing Manager, Afirah Shafiqnas binti Ramlee as the Operational Manager, Rosie ak Nanang as the Operational Manager and Benya ak Arun as Financial Manager. The selection for all managers is based on consensus among all the partners and the selected based on the experience, skill and ability. The management team will be led by the General Manager and assist by the other managers. The General Manager is responsible in planning, leading controlling and organizing the business. The Marketing Manager will be responsible to create the marketing plan, identifying the customer’s need and wants, identifying the competitors, target market, market size and forecast the future market. The Operational Manager is responsible to the entire job that related to the operation and will be supervising and coordinating the operation of the business. The Administration Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. Lastly, the Financial Manager will be handling the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.